PENGEMBANGAN MEDIA PAPAN PINTAR ANGKA - Vika Yusniar; Dewi Fitria; Juli Yanti Harahap (STKIP Subang, 2024)
This development aims to determine the feasibility of learning media, namely smart number board media. This research is a type of research and development or Research and Development (R&D) using stages with the development model used in this research being the ADDIE development model. According to Sugiyono in Sarinah (2020:48) the ADDIE development model consists of five stages which include analysis, design, development, implementation and evaluation. The Smart Number Board (PaPiKa) is a learning media that can make it easier for teachers to provide interesting and fun learning material for young children and is equipped with a guidebook for using the media which makes it easier for teachers to play the Number Smart Board (PaPiKa) media according to the stages. The results from the validator say that the media developed is Valid or Very Appropriate with material expert validation results of 83% and media expert validation 96% of these results, so it can be said that the number smart board media (PaPika) is Valid or Very Appropriate